2014
DOI: 10.1016/j.compmedimag.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional elastic image registration using B-spline affine transformation

Abstract: A registration scheme termed as B-spline affine transformation (BSAT) is presented in this study to elastically align two images. We define an affine transformation instead of the traditional translation at each control point. Mathematically, BSAT is a generalized form of the affine transformation and the traditional B-Spline transformation (BST). In order to improve the performance of the iterative closest point (ICP) method in registering two homologous shapes but with large deformation, a bi-directional ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As a spatial normalization procedure for two section images, which could be acquired at different times or from different locations, the images need to be registered so to find an optimal transformation to align the two images in the same coordinate system. Previously, there have been several algorithms developed for this purpose, particularly in the area of medical image analyses 10 11 12 . In the current study, to improve the calculating efficiency, section image registration and alignment were implemented using the bilinear method 13 .…”
Section: Resultsmentioning
confidence: 99%
“…As a spatial normalization procedure for two section images, which could be acquired at different times or from different locations, the images need to be registered so to find an optimal transformation to align the two images in the same coordinate system. Previously, there have been several algorithms developed for this purpose, particularly in the area of medical image analyses 10 11 12 . In the current study, to improve the calculating efficiency, section image registration and alignment were implemented using the bilinear method 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Chaitanya et al (2019) showed that visually nonrealistic synthetic examples can improve the segmentation of cardiac MRI and noted that it is slightly counter-intuitive-it may have occurred due to the inherent structural and deformationrelated characteristics of the cardiovascular system. Finally, elastic transformations often benefit from B-splines (Huang and Cohen, 1996;Gu et al, 2014) or random deformations (Castro et al, 2018). Diffeomophic mappings play an important role in brain imaging, as they are able to preserve topology and generate biologically plausible deformations.…”
Section: Data Augmentation Using Elastic Image Transformationsmentioning
confidence: 99%
“…The 120 CT scans in Dataset 1 used to develop the lung and vessel segmentation algorithm had the lung boundaries delineated and other types of lung diseases labeled by an experienced thoracic radiologist (D.P.). Our computational geometric approach [ 19 ] used to identify the intrapulmonary vessels often failed to identify the vessels near the hilum due to the entanglement of the arteries and veins. Therefore, the U-Net framework was used to identify the main extrapulmonary vessels and vessels near the hilum.…”
Section: Methodsmentioning
confidence: 99%